UTILIZING MARINE TRAFFIC APPLICATIONS FOR ELECTRONIC NAVIGATION SYSTEMS AND MONITORING COURSES ON CADET REPORTING WHEN IMPLEMENTING MARINE PRACTICE AT MALAHAYATI MERCHANT MARINE POLYTECHNIC - Bayu Yudho Baskoro; Rispa Saeful Mutamar; Syamsul Arifin; Mhd. Hennaufal (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
It is undeniable that one of the main causes of the globalization era, which is coming faster than all parties expected, is the rapid development of information technology. The implementation of the internet, electronic commerce, electronic data interchange, virtual office, telemedicine, intranet, and so on has broken through the physical boundaries between countries. The combination of computer technology with telecommunications has produced a revolution in the field of information systems. Data or information that in ancient times had to take days to be processed before being sent to the other side of the world, can now be done in seconds. It is no exaggeration if an IBM expert draws an analogy with automotive developments as follows: "If only the automotive world had progressed as fast as information technology, at this time a car with diesel fuel could be produced, which could be driven up to a maximum speed of 10,000 km/hour, with a purchase price of only about 1 American dollar. On a micro level, there are pretty interesting things to study, namely how the evolution of existing information technology developments significantly influences competition between companies in the world, especially those engaged in the service sector. Broadly speaking, there are four periods or eras of information system development, starting from the discovery of the first computer to the present.